Transitional Care in the Patient-Centered Medical Home: Lessons in Adaptation. Issue 2 (March 2017) - Hirschman, Karen B.; Shaid, Elizabeth; Bixby, M. Brian; Badolato, David J.; Barg, Ronald; Byrnes, Mary Beth; Byrnes, Richard; Streletz, Deborah; Stretton, Jean; Naylor, Mary D.
Abstract : Abstract: Older adults with multiple chronic conditions (MCCs) typically have risk factors (e.g., functional deficits, social barriers) that complicate the management of their healthcare, often with devastating human and economic consequences. Finding new ways to provide patient-centered care to community-based older adults with MCCs is essential. Two current models of care, the Patient-Centered Medical Home (PCMH) and the Transitional Care Model (TCM), have demonstrated improvements in the outcomes of high-risk older adults at different points on the chronic illness trajectory. However, neither care management approach has optimally engaged vulnerable patients to address needs throughout both acute and more stable transitions in health. In this article, we summarize the development of the PCMH plus TCM (hereafter, PCMH + TCM), an innovative approach to care, and the experience of the providers involved in testing the feasibility of implementing the PCMH + TCM. Using content analyses to code open-ended survey responses from transitional care nurses and PCMH clinical leaders', two major themes, collaboration and communication, emerged as critical to the process of implementing the PCMH + TCM. Barriers and facilitators to implementing the PCMH + TCM are presented. Findings support that the TCM can be adapted and integrated into the PCMH with meticulous planning and implementation.